Developing Active Reading Textbook For Third Semester Student Of English Study Program - Susilawati -; Mu’thia Mubasyira; Reknosari - (Peneliti.net, 2019)
This research is aimed to design the teaching material: Active Reading text book. The researchers applied the Pebble Pond Model to design the book. The model consists of six different phases namely, problem, progression, analysis, strategy, design and production. Merril (2002). The result of the research is expected to help the lecturers to teach active reading course and deliver the knowledge through the reading material to the students. After identifying students’ problem in comprehend ESL texts, analyzing the students’ needs, designing the draft, and arranging the materials, the researchers designed the book based on the available syllabus. The Active Reading book is designed to assist the students in learning reading at the third semester. The book consists of the reading material completed by the reading strategies. The various ESL texts will help the students be successful readers.